CONTENT CREATOR, DIGITAL MARKETING, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SKINCARE WARDAH MELALUI TOKOPEDIA DAN TIKTOK SHOP DI JAWA TIMUR - Amaliyah, Cinta Ayu; Muhajir, Ali; Arisandra, Martha Laila (J-EEMB (Journal of Economic Entrepreneurship and Management Business), 2025)
This research aims to determine the influence of Content Creator, Digital Marketing, and Product Quality on Wardah Skincare Purchasing Decisions on Tokopedia and TikTok Shop (Consumer Case Study in East Java). This study uses a quantitative approach with a survey method to 100 respondents. The analysis technique used is multiple linear regression with the help of the SPSS version 27 program. The results show that Content Creator obtained a score of 3,041, Digital Marketing obtained a score of 3,102, and Product Quality obtained a score of 3,477, which shows that these results have a significant effect on Purchasing Decisions, both partially and simultaneously. Product Quality is the most dominant variable in influencing Purchasing Decisions. The coefficient of determination (R Square) value of 0.856 indicates that 85.6% of the variation in Purchasing Decisions can be explained by these three variables, while the remaining 14.4% is explained by other factors outside the model. These findings emphasize the importance of strengthening digital strategies through Content Creator and Digital Marketing, as well as continuing to maintain Product Quality to improve consumer Purchasing Decisions in the e-commerce market.